2016
DOI: 10.1038/emm.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent progress of reprogramming and gene correction to overcome therapeutic limitation of mutant ALK2-iPSC

Abstract: Fibrodysplasia ossificans progressiva (FOP) syndrome is caused by mutation of the gene ACVR1, encoding a constitutive active bone morphogenetic protein type I receptor (also called ALK2) to induce heterotopic ossification in the patient. To genetically correct it, we attempted to generate the mutant ALK2-iPSCs (mALK2-iPSCs) from FOP-human dermal fibroblasts. However, the mALK2 leads to inhibitory pluripotency maintenance, or impaired clonogenic potential after single-cell dissociation as an inevitable step, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…In fulfilling this task, there are several available conditional knock-in or transgenic mouse models in which constitutively active ALK2 is expressed [9, 11]. In addition, induction of iPS cells derived from FOP to osteoblast differentiation and transplantation of the differentiated cells into nude mice has emerged as another type of model that is useful in studying the mechanism of HO, and for testing efficacy of drugs in the treatment of FOP [37, 38]. As such, it will be intriguing to apply clinically available AMPK activators to these FOP models.…”
Section: Discussionmentioning
confidence: 99%
“…In fulfilling this task, there are several available conditional knock-in or transgenic mouse models in which constitutively active ALK2 is expressed [9, 11]. In addition, induction of iPS cells derived from FOP to osteoblast differentiation and transplantation of the differentiated cells into nude mice has emerged as another type of model that is useful in studying the mechanism of HO, and for testing efficacy of drugs in the treatment of FOP [37, 38]. As such, it will be intriguing to apply clinically available AMPK activators to these FOP models.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of iPSc in vitro rapidly and effectively indicates the phenotype of disease in an individual specific background. A variety of somatic cells can be (54) reprogrammed into stem cells, including skin fibroblasts (32) and kidney epithelial cells (48), and Sendai virus and non-integration vector can be used as programming tools (49). (50).…”
Section: Cells Models Of Fopmentioning
confidence: 99%
“…A recent study suggested that a one-step procedure can generate gene-corrected ALK2-iPSCs, and the advantages of this approach are that it saves time, labor, and money (83). Activated BMP signaling by an FOP R206H mutation adversely affects the generation of FOP iPSCs since BMPs can induce differentiation of human ESCs (84).…”
Section: Cell Therapymentioning
confidence: 99%